Learning needs analysis of english-majored students from five gifted high schools in the Mekong Delta : - Nguyễn, Thị Thu Ái (Trường Đại học Cần Thơ, 2020)
In Vietnam, the debate about whether or not to retain the specialized school system is ongoing. However, the Ministry of Education and Training of Vietnam indicated that students from gifted high schools play the role as “a spike” in Vietnamese education system. It is also applied for the quality of English-majored students. Therefore, to understand the strengths and the shortcomings of these students in English learning, this study was conducted to investigate their perceptions of the importance of English for their future competition, what skills they want to improve most at present, and their learning needs of the language knowledge and skills, which especially makes them different from public high school ones. The study employed a mixed method of a thirty-eight-item survey and interviews. One hundred and eighty twelfth-grade students took part in the survey and ten were interviewed. The research results revealed that most of the students believed that learning English is essential to get good jobs in the future. In addition, the students had high demand for language knowledge and skills. However, their needs of speaking skills were the most significant and they expected to be engaged more in speaking in the classroom. More importantly, the learning programs failed in fulfilling most participants’ learning needs of specified components and skills while they well met the participants’ demand for the national exam. Based on the findings, this study suggested some implications for meeting English majored-students’ learning needs throughout the Mekong Delta, Vietnam.